Optimizing Educational Excellence: Unveiling SMA Darul Ulum 2 Jombang's Successful Integration of the Seven Correlates of Effective Schools - Zulfikar, Afifa Syamsun (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines the holistic approach to education practiced at SMA Darul Ulum 2 in Jombang, Indonesia, within the context of pesantren schools. Pesantren schools blend Islamic values with general knowledge, presenting a unique educational model. Despite their role in fostering strong moral values, these schools encounter challenges in curriculum development and infrastructure. Traditional emphasis on religious sciences sometimes results in a perceived gap compared to public schools, highlighting the need for balance between religious and academic education. Through innovative strategies, SMA Darul Ulum 2 aims to integrate religious teachings with modern educational practices. The study employs qualitative methods, including interviews and observations, to explore how SMA Darul Ulum 2 implements effective school practices, focusing on Lezotte's Seven Correlates of Effective Schools. Findings reveal a comprehensive approach to education, integrating moral and academic development. The principal's leadership, teacher commitment, clear mission alignment, and positive school-home relations contribute to the school's success. These findings underscore the importance of effective leadership and strategic management in achieving educational excellence.